Power and precariousness in the expert hierarchies of the US hydrocarbon industry. (September 2021) - Field, Sean
Drawing on ethnographic research in Houston, Texas, I explore how oil and gas experts negotiate social power and precariousness within the US hydrocarbon sector. In an industry long associated with corporate power, the careers of experts are precariously balanced on rising and falling hydrocarbon prices. This makes the social power these experts wield as fluid as the commodities they are premised on. I show that informal social networks solidified by industry associations can buffer this precariousness by opening new employment opportunities and allowing them to maintain their connection to elite industry circles through periods of unemployment and uncertainty. For many working in the industry, precariousness defines the US hydrocarbon sector as much as the wealth that it is known to generate. Precariousness, I argue, is not just experienced by specific groups of people but rather is a general characteristic of capitalism that touches all but a select few.